ANALYSIS OF THE INFLUENCE OF FINANCIAL DEVELOPMENT AND FINANCIAL INCLUSION ON ECONOMIC GROWTH - Luluis Zaqiyah; Hery Sulistyo Jati Nugroho Sriwiyanto (Journal of Applied Economics in Developing Countries, 2022)
The objective of this research is to analyze the influence of financial development, represented by credit/GRDP and MSME/GRDP credit, and financial inclusion, represented by the number of bank branches per 100,000 adult population and third-party funds per GRDP, on economic growth in 33 Indonesian provinces during the 2013-2017 period. The data in this study used 33 provinces in Indonesia. The method of analysis is the panel data method. The data panel is a combination of time series data and cross-sections. The cross-sectional data is processed by observing the same object in a different way and at different times. This study found that financial development had a significant positive effect based on credit / GRDP variables. meanwhile, the SMEs / GDP credit proceeds were found to be insignificant in economic growth. Financial inclusion has a negative and significant effect based on a variable number of offices. Bank branches per 100,000 adult population and DPK / GRDP at current prices. At the same time, the control variables collected were significant and positive capital, while the labor force was not significant.